(untitled) (Dimensión Empresarial, 2017)
The objective proposed in this paper is to demonstrate the importance of the fundamental factors in the functioning and competitiveness of the clúster. A survey was applied to hoteliers and restaurateurs of the tourist destination of the city of Oaxaca, with information obtained correlation analysis and regression factors were made. The results show that there is a positive relationship between the factors of cooperation, social networks, knowledge and innovation, and these same relate to competitiveness. The trust factor is related to competitiveness, but showed no relation to the other fundamental factors. According to the regression knowledge and innovation are the factors that explain the competitiveness of the companies surveyed. This shows the importance of the fundamental factors for the clúster, which should be considered when implementing a clúster policy and achieve increased competitiveness. Resumen El presente artículo es resultado de una investigación científica y se ha planteado en torno al objetivo de analizar y comparar la influencia de las características personales y sociales en la predisposición a innovar en los consumidores jóvenes de Villavicencio - Colombia y Coatzacoalcos - México. Para el desarrollo se procedió a encuestar a 1591 jóvenes universitarios de las dos ciudades. El rango etario de la muestra fue entre 17 y 25 años. Para ello se contó con la colaboración de la Universidad de los Llanos y la Universidad Veracruzana. Los resultados evidencian que no existe asociación entre la predisposición a innovar y las variables de características personales o sociales estudiadas. Esto significa que una estrategia de segmentación demográfica no es suficiente, pues los determinantes del comportamiento del segmento pueden estar influenciados por sus motivaciones personales, o por las características de los productos. Resumo Este artigo é o resultado da investigação científica e tem sido levantada em torno do objetivo analisar e comparar a influência das características pessoais e sociais na predisposição para inovar jovens consumidores de Villavicencio - Colômbia e Coatzacoalcos - México. Desenvolvimento procedeu ao levantamento de 1591 estudantes universitários das duas cidades. A faixa etária da amostra foi de entre 17 e 25 anos. Para fazer isso, ele contou com a colaboração da Universidade do Llanos e Universidad Veracruzana. Os resultados mostram que não existe uma associação entre a vontade de inovar e variáveis de características pessoais ou sociais estudados. Isto significa que uma estratégia de segmentação demográfica não é suficiente, porque os determinantes do segmento de comportamento podem ser influenciados pelas suas motivações pessoais, ou as características dos produtos.